Data Protection Compliance in the UK : a Pocket Guide. - Jay, Rosemary (IT Governance Pub., 2010)
This book gives you a clear description of the Data Protection Act, outlining its terms and explaining its requirements. It is essential reading if you have a responsibility for the security of personal data, especially if you are a director, a manager or an IT professional. The pocket guide includes handy good practice tips for staff. The easy-to-follow checklist tells you the practical steps you should be taking in order to comply with the Data Protection Act.